Performance and success factors in biathlon - Lopatic, S. (International Journal of Academic Health and Medical Research, 2022)
Biathlon is a combination of two completely different sports - Nordic skiing and archery. While cross-country skiing requires great physical effort, archery requires a clear head and a calm and relaxed body. The aim of this study was to determine the factors that affect the accuracy and shooting of targets in biathlon. Due to the reduced number of researches in this field, five papers were singled out in the period between 2011 and 2018. By reviewing the literature, we can conclude the great role of the postural status of every biathlete. Whether the shooting is performed from a lying or upright position, a special focus is on stabilizing the aiming point before the shot is fired. Better shooting results are significantly related to the smaller distance of the middle location of the target point.